Change of the Ideas of Science Teachers After Participation in a Training Program on the Use of Non-Formal Educational Places - Vanegas-Ortega, C (University of Helsinki, 2018)
Absract: The objective of this study is to understand how the perception of teachers might change after they participate in a training program on the use of non-formal educational places (NFEP). The design of the study is ethnographic and its methodology is qualitative. The study comprehends the analysis of three multiple cases according to the disciplinary area, including teachers of primary education, biology, and physics. The analysis was focused on the discourse of the participants, establishing eight categories which were previously validated through triangulation by time and by instruments. The study concludes that the participants were able to restructure their ideas about the use of NFEP for teaching, showing mainly ontological and epistemological changes, which are discussed in the paper. © 2018 University of Helsinki. All Rights Reserved.